The DNP by 2015 A Study of the Institutional, Political, and Professional Issues that Facilitate or Impede Establishing a Post-Baccalaureate Doctor of Nursing Practice Program - Auerbach, David I. (RAND Corporation, 2015)
In 2004, members of the American Association of Colleges of Nursing approved the position that all master's programs for advanced-practice registered nurses should transition to doctorate of nursing programs by 2015. This report describes the results of a RAND study seeking to understand nursing school program offerings and the reasons for those offerings, as well as the barriers or facilitators to full adoption of doctorate programs.